A Comparative Study of Sexual Dysfunction in Schizophrenia Patients Taking Aripiprazole Versus Risperidone - Shah, SK (Kathmandu University Medical Journal, 2015)
Background Sexual dysfunction due to antipsychotics is a significant problem encountered with first-generation antipsychotics. Even the second-generation antipsychotics like risperidone are not free of sexual dysfunction due to its D2 blocking properties leading to hyperprolactinaemia. Newer antipsychotic aripiprazole, partial dopamine agonist, with neutral effect on prolactin level or even decreasing it, is associated with avoidance of sexual dysfunction. Objectives To assess the effect of risperidone and aripiprazole on sexual function of schizophrenic patients. Methods This was an open-label, cross-sectional, observational study conducted at College of Medical Sciences, Bharatpur. Schizophrenic patients attending OPD and inpatient, taking risperidone or aripiprazole for at least two months were included in this study. Forty one patients, without chronic medical illness and sexual dysfunction before starting drugs, with informed consent were studied during Jan 2012 and Aug 2012. Results Changes in sexual activity was found in 11(55%) of those taking risperidone while, only 3(14.3%) had any kind of sexual difficulty. This was statistically significant (p=0.006). Majority, 92.7% of the patients did not report about changes in sexual activity spontaneously. Conclusion Sexual dysfunction was statistically significantly higher in those taking risperidone. Prevalence of sexual dysfunction was low with aripiprazole. Except those having poor sexual functions due to the drugs, the majority had to be specifically inquired about the effects of drug on sex life. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12486 Kathmandu University Medical Journal Vol.11(2) 2013: 121-125